Efisiensi Kerja Pemboran Eksplorasi Pada PT Vale Indonesia: Efficiency of Exploration Drilling Work at PT Vale Indonesia - Hasbi Bakri; Alam Budiman Thamsi; Sahabuddin Sahabuddin (Journal of Engineering Science and Technology Applications, 2023)
Exploration activities nickel (Ni) which is one of the stages, is where the exploratory drilling work efficiency is one of the main factors that can describe how good a job has been done. The purpose of this study is to analyze the efficiency of exploration drilling. This research method is done by direct observation in the field. The data that was obtained was a record time of any activities during the working day in the form of exploration drilling activity, inserting the inner tube in the core barrel, an empty lap, then taking out further drilling in the core barrel inner tube, prepare the inner tube, add pipes, and re-inserting the inner tube core barrel. There are other activities that the problems of the inner tube not landing. The inner tube can not rise, smoothing supplies drilling, pulling out the pipe, moving the drilling tool and equipment, preparation of drilling, transportation, accessibility, preparatory work crew, safety talk/meeting, checking tool, refueling, wait for dozer, crew return preparations, waiting for a supervisor/geologist, waiting for the crew, weather problems, rest, waiting to go home, repair, and water issues. This study obtained an efficiency increase of 44.43% in drilling work. Concluded the drilling work efficiency is still below the working efficiency standards applied by the company by 50%.